Infinite Systems of Hyperbolic Functional Differential Equations - Kamont, Z. (Український математичний журнал, 2003)
We consider initial-value problems for infinite systems of first-order partial functional differential equations. The unknown function is the functional argument in equations and the partial derivations appear in the classical sense. A theorem on the existence of a solution and its continuous dependence upon initial data is proved. The Cauchy problem is transformed into a system of functional integral equations. The existence of a solution of this system is proved by using integral inequalities and the iterative method. Infinite differential systems with deviated argument and differential integral systems can be derived from the general model by specializing given operators. Розглядаються початкові задачі для нескінченних систем функціональних диференціальних рівнянь першого порядку з частинними похідними. Доведено теорему про існування розв'язку та неперервну залежність від початкових даних. Задачу Коші трансформовано у систему функціональних інтегральних рівнянь. Існування розв'язку цієї системи доведено за допомогою інтегральних нерівностей та ітераційного методу. Нескінченні диференціальні системи з аргументом, що відхиляється, та диференціальні інтегральні системи можна отримати із загальної моделі шляхом спеціалізації заданих операторів.